Research on statistical tables and graphs in primary education textbooks in Latin America: literature review (Innovaciones Educativas, 2021)
This article reports a literature review regarding research on statistical tables and graphs in primary school textbooks in Latin America, with the aim of providing the reader with an overview of what has been developed and some implications for the future. Under a qualitative methodology, a systematic review of the literature of the last 15 years was carried out, in five stages: 1) planning, 2) search, 3) selection, 4) quality evaluation, and 5) extraction and synthesis. The search was carried out in the open access database Education Resources Information Center (ERIC) and in the search engines Google Scholar and Semantic Scholar. From the search results, 39 investigations were selected: 29 published in journals and 10 in conference memoires. Among the findings, the geographic diagram shows a broad exploration and concentration of the research line only in some countries, with a focus on exploring the quality of activities and/or identifying the type of statistical representation used and its complexities to resolve tasks. In addition, a great variety of analysis units used for the development of these investigations is identified, placing them in analyzing the reading level, the level of semiotic complexity, the requested task and the type of context of the activities in which the tables and statistical graphics appear.
Keywords: statistical table; statistical graph; textbook; statistics; basic education